The Birds of Small Islands off the Eastern Coast of Panay - Alcala, Angel C.; Sanguila, Warlito M. (Silliman Journal, 2024)
The authors, in April and May, 1969, visited the islands off the eastern coast of Panay to study their bird and mammal populations. The authors felt urgent need for the study because the continuing destruction of the forests there could lead to the extinction of these birds and mammals. The authors found that the birds in these islands are similar to those in Negros.